Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

This is part of Exercise III.1.16(c) of Bourbaki's set theory.

Let $E$ be a lattice. The condition

$(x\vee y)\wedge(z\vee(x\wedge y))=(x\wedge y)\vee(y\wedge z)\vee(z\wedge x)$

for all $x,y,z\in E$ implies that $E$ is distributive.

I already know that

$(x\vee y)\wedge(y\vee z)\wedge(z\vee x)=(x\wedge y)\vee(y\wedge z)\vee(z\wedge x)$

implies distributivity, so it suffices to prove

$(x\vee y)\wedge(z\vee(x\wedge y))=(x\vee y)\wedge(y\vee z)\wedge(z\vee x)$.

I can't find a proof of this last statement. Either it is true in any lattice, then the proof should be so simple I must be blind not to see it, or I have to use the condition above again, but I can't imagine in what way.

share|improve this question
1  
To see the last equality does not hold for arbitrary lattices, take the 5-element $01$-lattice with $x,y,z$ pairwise distinct, and with all three pairwise joins among them equal to $1$, and all three pairwise meets equal to $0$ (the diamond lattice $M_3$). Then the left hand side evaluates to $z$, the right hand side evaluates to $1$. –  Arturo Magidin Dec 18 '10 at 22:14

1 Answer 1

up vote 2 down vote accepted

$(x\vee y)\wedge(z\vee(x\wedge y))=(x\wedge y)\vee(y\wedge z)\vee(z\wedge x)$

implies

$x\vee((x\vee y)\wedge(z\vee(x\wedge y)))=x\vee((x\wedge y)\vee(y\wedge z)\vee(z\wedge x)).$

The right side equals $x\vee(y\wedge z)$.

For the left side, we use the condition above again, substituting $x\vee y$ for $y$ and $z\vee(x\wedge y)$ for $z$, and get

$x\vee((x\vee y)\wedge(z\vee(x\wedge y)))=(x\vee y)\wedge((z\vee(x\wedge y))\vee x)=(x\wedge y)\vee(x\wedge z).$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.